2021
DOI: 10.1093/jas/skab185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein sources and inclusion levels on nitrogen metabolism and urea kinetics of Nellore feedlot steers fed concentrate-based diets

Abstract: Urea recycling occurs in all mammalian species and represents an important source of ruminal nitrogen (N) for ruminants fed protein-restricted diets. However, its importance for cattle fed adequate amounts of protein and energy remains unclear. Six Nellore feedlot steers fed concentrate-based diets were used in a 6 × 6 Latin square design with a 3 × 2 factorial arrangement of treatments to evaluate ruminal fermentation, urea kinetics, and N excretion. Treatments consisted of 3 protein sources (PS: soybean meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Alternatively, the use of DMI may lead to lower cumulative error compared to NI, which requires the measurement of N content in feed samples ( Hristov et al., 2019 ). In contrast, urinary and manure N were best predicted from NI rather than DMI, which was expected as N intake is the major driver of urinary N excretion ( Dijkstra et al., 2013 ) and urine is the major route of excretion of surplus N in beef cattle ( Souza et al., 2021 ). It is well-documented that ruminal ammonia concentration increases in high CP diets ( Souza et al., 2021 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Alternatively, the use of DMI may lead to lower cumulative error compared to NI, which requires the measurement of N content in feed samples ( Hristov et al., 2019 ). In contrast, urinary and manure N were best predicted from NI rather than DMI, which was expected as N intake is the major driver of urinary N excretion ( Dijkstra et al., 2013 ) and urine is the major route of excretion of surplus N in beef cattle ( Souza et al., 2021 ). It is well-documented that ruminal ammonia concentration increases in high CP diets ( Souza et al., 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, urinary and manure N were best predicted from NI rather than DMI, which was expected as N intake is the major driver of urinary N excretion ( Dijkstra et al., 2013 ) and urine is the major route of excretion of surplus N in beef cattle ( Souza et al., 2021 ). It is well-documented that ruminal ammonia concentration increases in high CP diets ( Souza et al., 2021 ). The ammonia not incorporated into microbial CP can be absorbed across the ruminal wall, entering the portal vein, and transported to the liver, where it is largely converted to urea ( Batista et al., 2017 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chikhou et al [ 31 ] showed that the level of BUN in plasma could reflect the protein metabolism of animals and could be used as an indicator of the body’s protein decomposition status. Under the condition of a low nitrogen diet, ruminants mainly increased nitrogen deposition through the BUN cycle; thus, the content of BUN increases to meet the needs of the body [ 32 ]. Compared with Brahman, Yunling cattle have higher BUN and lower URIC levels, indicating that Yunling cattle have a better roughage tolerance than Brahman, which is consistent with the actual production.…”
Section: Discussionmentioning
confidence: 99%